Evaluation of environmental contamination of the effluent from the oxidation well of the district of Daniel Hernández, Tayacaja-2023 - Chavarría Marquez, Esmila Yeime (2023)
It will be prolonged that the Upamayo river is contaminated due to the effluent from the oxidation pond of the Daniel Hernández district of the Tayacaja province, since the quality standards exceed the parameters of pH, fecal coliforms, Escherichia coli, TSS and salinity for water intended for animal drinking. Likewise, they exceed the environmental quality standards (ECA) in pH, Escherichia coli, TSS and salinity for unrestricted irrigation waters. In that, the mitigation alternatives to this problem will be the reduction of the discharge mouth of the oxidation pond, optimization of disinfection before the effluent is discharged, the application of projects to fines to increase the flow of the Upamayo river, the inclusion of a phytoremediation system within the ponds of oxidation or the execution of a public investment project for the construction of a large-scale wastewater treatment plant (PTAR).